Systematic Literature Review: Layanan Konseling Kelompok Sebagai Upaya Meningkatkan Rasa Percaya Diri Siswa - Putri Ardila; Imelda Aprillia Sitanggang; Muhammad Ariq Musthofa; Nabila Destriyanti; Dirham Alkayisa Tayyara Tazkia; Siti Hamidah (Jurnal Pendidikan Sosial Dan Konseling, 2024)
Students' self-confidence plays a very important role in encouraging students to develop their potential. However, many students still feel less confident or insecure, which hinders their development. Seeing this problem, efforts need to be made to help students so that their self-confidence can grow and increase so that they can develop their potential to achieve a future according to what they want. This study aims to raise awareness regarding the need for group counseling services so that students can increase their self-confidence. Group counseling services can be carried out with BK teachers at school. This is an effort to form quality students with high self-confidence. The research method used is the Systematic Literature Review (SLR) method. Systematic Literature Review (SLR) using the PRISMA (Preferred Reporting Items For Systematic Reviews And MetaAnalyses) guidelines as a tool for selecting data sources used. Based on the research conducted, it was found that group counseling services carried out by BK teachers for students at school were able to increase self-confidence, especially for students. The results of the research conducted found that there was a difference in the level of students' self-confidence before and after conducting group counseling. The results of this study indicate that students' self-confidence gradually developed to be better when compared to the level of students' self-confidence before conducting group counseling services.